Standards-Based Computing Capabilities for Distributed Geospatial Applications. - Lee, C.; Percivall, G. (Computer (00189162), 2008)
Researchers face increasingly large repositories of geospatial data stored in different locations and in various formats. To address this problem, the Open Geospatial Consortium and the Open Grid Forum are collaborating to develop standards for distributed geospatial computing.